German Heart Surgery Report 2018: The Annual Updated Registry of the German Society for Thoracic and Cardiovascular Surgery - Beckmann, Andreas; Meyer, Renate; Lewandowski, Jana; Markewitz, Andreas; Harringer, Wolfgang (The Thoracic and Cardiovascular Surgeon, 2019)
Based on a longtime voluntary registry, founded by the German Society for Thoracic and Cardiovascular Surgery (GSTCVS), well-defined data of all cardiac, thoracic, and vascular surgery procedures performed in 78 German heart surgery departments during the year 2018 are analyzed. For this period, a total of 174,902 procedures were submitted to the registry, 98,707 summarized as heart surgery procedures in the classical meaning. The unadjusted in-hospital survival rate for 33,999 isolated coronary artery bypass grafting procedures (relationship on-/off-pump 3.8:1) was 97.1% and for 34,915 isolated heart valve procedures, 14,396 transcatheter interventions included, it was 96.0%. Concerning short- and long-term circulatory supports, a total of 2,871 extracorporeal life support (ECLS)/extracorporeal membrane oxygenation (ECMO) implants, respectively, 942 assist device implantations (L-/R-/BVAD, TAH) were registered. In 2018, the number of isolated heart transplantations increased to 312, a growth of 23% compared with the previous year. The isolated lung transplantations reached 340, a rise of nearly 19%. This annual updated registry of the GSTCVS represents voluntary public reporting by accumulating actual information for nearly all heart surgical procedures in Germany, constitutes advancements in heart medicine, and is a basis for quality management for all participating institutions. In addition, the registry demonstrates that the provision of cardiac surgery in Germany is appropriate and nationwide patient treatment is guaranteed all the time.
Keywords: heart valve procedures; heart surgery; mortality; congenital heart disease; coronary heart disease; aorta surgery; coronary artery bypass grafting; heart and lung transplantation